Economic Factors and Performance of Selected Quoted Consumer Goods Manufacturing Companies: The Moderating Roles of Firm Agility - Adedoyin Opeyemi Okusanya; Adeolu Oludare Olatoye; Taiwo Olubunmi Keinde; Adebola Ademola Adebayo (Universitas Pendidikan Ganesha, 2024)
The problem of this study is the significant decline in the performance of consumer goods manufacturing companies, which is caused by various economic factors such as import policies, inflation, infrastructure, interest rates, and exchange rates. This study aims to evaluate the impact of economic factors on the performance of publicly traded consumer goods manufacturing companies and test how corporate agility moderates this relationship. The study employed a cross-sectional survey design with a population of 5,625 employees from 12 companies, yielding a final sample of 563. Data was collected through a questionnaire validated by confirmatory factor analysis and measured by a Likert scale. Data analysis was conducted with multiple regression using SPSS version 22.0. The results show that economic factors significantly affect firm performance, and firm agility significantly moderates this relationship. The conclusion of this study suggests that consumer goods manufacturing companies need to improve their agility to overcome the negative impact of economic factors. This study implies the need for more adaptive and flexible management strategies to enhance firm performance in the face of dynamic economic challenges.